A three-decade outburst of the LMC luminous blue variable R127 draws to a close - Walborn, Nolan Revere (2008)
The paradigmatic luminous blue variable R127 in the Large Magellanic Cloud has been found in the intermediate, peculiar early-B state, and substantially fainter in visual light, signaling the final decline from its major outburst that began between 1978 and 1980. This transformation was detected in 2008 January, but archival data show that it began between early 2005 and early 2007. In fact, significant changes from the maximum, peculiar A-type spectrum, which was maintained from 1986 through 1998, had already begun the following year, coinciding with a steep drop in visual light. We show detailed correspondences between the spectrum and light, in which the decline mimics the rise. Moreover, these trends are not monotonic but are characterized by multiple spikes and dips, which may provide constraints on the unknown outburst mechanism. Intensive photometric and spectroscopic monitoring of R127 should now resume, to follow the decline presumably back to the quiescent Ofpe/WN9 state, in order to fully document the remainder of this unique observational opportunity.